2006
DOI: 10.1627/jpi.49.315
|View full text |Cite
|
Sign up to set email alerts
|

Water Accumulation and Behavior of Surfactant Associated with Moisture Permeation in Bituminous Pavement on Concrete Deck Bridge

Abstract: Water-related damage is one of the major problems for the durability of the bituminous pavement and concrete slabs of concrete deck bridges. In particular, damage can be drastically accelerated by the intervention of water and some chemicals such as surfactants and salts. Therefore, the mass transfer mechanism of water and the mechanism of chemical absorption in pavement materials are important to study. The authors previously pointed out that water storage in bituminous pavement layers is caused by moisture v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…(1) Determination of emission sources of organic matter suggested that cement concrete absorbs airborne organic matter together with moisture as it "breathes" like animals and plants when the time difference between surface and bottom temperature exists [9]. The components of organic matter detected in TSM were the same as those in the tire samples and DEP, except for DOP, which was detected only in the tire.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) Determination of emission sources of organic matter suggested that cement concrete absorbs airborne organic matter together with moisture as it "breathes" like animals and plants when the time difference between surface and bottom temperature exists [9]. The components of organic matter detected in TSM were the same as those in the tire samples and DEP, except for DOP, which was detected only in the tire.…”
Section: Resultsmentioning
confidence: 99%
“…The aspiration phenomena of cement concrete was examined in laboratory. The anion type surfactant on the surface of asphalt pavement on concrete bridge (asphalt layer: 4 cm + 4 cm, cement concrete: 4 cm) easily penetrated into the cement concrete of bottom layer, under the time difference of temperature change of pavement surface and bottom of cement concrete, and decalcified the cement concrete [9].…”
mentioning
confidence: 99%
“…This result suggests that trace quantities of organic matter (TQOM; phthalates, SPNES, amine compounds, and hydrocarbon) in the air are absorbed in concrete structures by the concrete respiratory action. It was reported in the results of the concrete slab damaged by small concentrations (1.6 g) of SPNES on the surface of the asphalt pavement in the core sample of a new concrete bridge using repeated transient moisture permeation tests (46 times: it corresponds to 46 days) reported in section 3.11 [ 15 ]).…”
Section: Resultsmentioning
confidence: 99%
“…Based on this it was decided, to use polyoxyethylene nonylphenyl ether sodium sulfate, an anion surfactant, in the immersion experiments, as this would cause the elution of the calcium in the cement concrete, which would turn the solution cloudy, showing when calcium salts were generated [17] and [20].…”
Section: Icp (Emission Spectral Analysis)mentioning
confidence: 99%